Pengaruh Ukuran Koperasi, Profitabilitas, dan Pertumbuhan Terhadap Struktur Modal - Winata, Indra; Indriani, Yuanita; Setiawati, Rosti (Coopetition : Jurnal Ilmiah Manajemen, 2025)
The aim of this study is to analyze the influence of cooperative size, profitability, and growth on capital structure both simultaneously and partially in primary consumer cooperatives in regencies/cities in West Java Province that submit performance reports to the Ministry of Cooperatives and SMEs through the Cooperative Online Data System regularly for the period 2018-2022. The research method uses quantitative research, and path analysis through the SPSS 25.0 program. The sample population are491 primary consumer cooperatives in Regency/City in West Java Province that submit reports to the Ministry of Cooperatives and SME or the Office in charge of Cooperatives and SME through the Cooperative Online Data System managed by the Ministry of Cooperatives and SME. The results showed that the size of the cooperative has a significant influence on the capital structure of primary consumer cooperatives in the Regency/City in West Java Province with a negative direction, profitability has a significant influence on the capital structure of primary consumer cooperatives in the Regency/City in West Java Province with a negative direction, growth and profitability have a significant influence on the capital structure of primary consumer cooperatives in West Java Province. The results showed that the size of the cooperative has a significant influence on the capital structure of primary consumer cooperatives in the Regency/City in West Java Province with a negative direction, profitability has a significant influence on the capital structure of primary consumer cooperatives in the Regency/City in West Java Province with a negative direction, growth does not have a significant influence on the capital structure of primary consumer cooperatives in the Regency/City in West Java Province. Simultaneously, cooperative size, profitability and growth have a significant influence on capital structure with a weak and unidirectional (positive) relationship.